Design And Build Information System For Land Certificaton Of Land Office In Sidoarjo Regency : Rancang Bangun Sistem Informasi Sertifikasi Tanah Kantor Pertanahan Kabupaten Sidoarjo - Rizky Fajar Ryandi; Yulian Findawati (Universitas Muhammadiyah Sidoarjo, 2020)
The purpose of this study is to build an information system for Land Certification in the Land Office of Sidoarjo Regency. This information system is a form of development in facilitating prospective applicants for making land easier and faster. To support the performance of the Sidoarjo Regency Land Office staff and make it easier for users to make land certificates. In this study, the method used was SDLC according to Ian Sommerville (2011). The cycle of stages contains requirement definition, system and software design, implementation and unit testing, integration and system testing, operation and maintenance so that the implementation can be maximized. The results of this study have built a Land Certification-based information system which greatly facilitates the performance of the Sidoarjo Regency Land Office staff. The conclusion from the research and discussion is that the Land Certification information system is running well and smoothly. With the existence of a land information system, it is hoped that it can help the work of BPN office officers, so that the efficiency and effectiveness of service performance can be improved as well as accelerating officer services for land-making transactions in Sidoarjo Regency.